The Influence of Service and Work Discipline on Employee Performance - Andika, Yori; Sovia, Arina; Zulsantoni, Zulsantoni; Dakhyar, Dakhyar (CV. Strata Persada Academia, 2024)
This research was motivated by the lack of service and work discipline on employee performance at the Pantai Cermin Subdistrict Office, Solok Regency. The method used in this research is a quantitative descriptive method, where data is obtained by distributing questionnaires to respondents. The respondents were all employees and staff of the sub-district office, as well as the people of Pantai Cermin District. The number was 50 respondents. Data analysis used Multiple Regression Analysis with the SPSS for Windows 26 computer program. The results showed that at the Pantai Cermin District Head Office, Solok Regency: (1) Respondent Achievement Level (TCR) for services with an average of 4.14 with a percentage of 82.90 including good category, average work discipline TCR 4.27 with a rate of 85.4 including the Good category and performance TCR with an average of 4.3 or with a rate of 85.4 including the Good category. (2) The service variable with a t-statistic value of 2.948 at a significance level of 0.005 is greater than the t-table of 1.679. This means that the service variable has a significant influence on the performance variable, so Ho1 is rejected and Ha1 is accepted. (3) The work discipline variable with a t-statistical value of 2.557 at a significance level of 0.014 is greater than the t-table of 1.679. This means that the work discipline variable has a significant influence on performance, so Ho2 is rejected and Ha2 is accepted. (4) From the results of the first test, the ANOVA test or F test can be concluded that the service and work discipline variables on performance variables simultaneously or together obtained a t-statistical value of 24.302, which is greater than the F-table 3.20 with a significance value of 0.000 < 0, 05 then Ho3 is rejected and Ha3 is accepted.